(untitled) ("Conference on Universal Science Research 2023", 2023)
This article is the life of Zahiriddin Muhammad Babur, activity, rich and colorful creative-scientific heritage and to the poet by our state the attention given to youth education of the poet’s works today and is devoted to the importance of non-existence in his scientific life.